1994
DOI: 10.1128/iai.62.5.2108-2110.1994
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae O139 synonym bengal is closely related to Vibrio cholerae El Tor but has important differences

Abstract: Although Vibrio cholerae O139 synonym Bengal strains, from the current epidemics in India and Bangladesh, are closely related to seventh-pandemic strains, as shown by multilocus enzyme electrophoresis, Bengal strains are encapsulated and portions of the O1 antigen biosynthetic complex genes found in O1 strains are altered or lacking. Encapsulated Bengal strains showed resistance to killing by normal human serum. The presence of the capsule suggests the potential for bloodstream invasion in susceptible hosts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(69 citation statements)
references
References 10 publications
1
67
0
1
Order By: Relevance
“…Vibrio cholerae O1 El Tor biotype as well as O139 serogroup possess mannose-sensitive haemagglutinin (MSHA), which is required for colonization to zooplankton (Chiavelli et al, 2001). However, it is well documented that V. cholerae O139 possesses a capsular polysaccharide and a different lipopolysaccharide, whereas O1 strains do not (Johnson et al, 1994;Knirel et al, 1995Knirel et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio cholerae O1 El Tor biotype as well as O139 serogroup possess mannose-sensitive haemagglutinin (MSHA), which is required for colonization to zooplankton (Chiavelli et al, 2001). However, it is well documented that V. cholerae O139 possesses a capsular polysaccharide and a different lipopolysaccharide, whereas O1 strains do not (Johnson et al, 1994;Knirel et al, 1995Knirel et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Outer-membrane lipopolysaccharide (LPS) of both 0 1 serotypes, Inaba and Ogawa, have a long 0-side chain identified as a homopolymer of 4-(3-deoxy-~-glycero-tetronamido)-4,6-dideoxy-~-mannose [4, 51 terminated in the latter serotype with the 2-0-methyl derivative of the same monosaccharide [6]. In contrast, K cholerae 0139 produces a polysaccharide capsule [2,71 and has an LPS with a short 0-side chain [7-91. Serological and genetic studies suggested that in V cholerae 01 We now report structural characterization, including data on both the 0-side chain and the core-lipid A region, of the LPS from V cholerue 0139 CPS-free mutant strains M010-T4 with the complete LPS and Bengal-2R with a truncated LPS. The preliminary results were presented at the XVIIIth International Carbohydrate Symposium (Milan, July 1996) [I 81.…”
mentioning
confidence: 99%
“…The disease affected mainly adults suggesting that, despite the epidemic in this area a year or more earlier, the population continued to be immunologically naive. The organism is itself considered to be closely related to Vibrio cholerae El Tor, with additional virulence factors (Calia et al 1994;Johnson et al 1994). The disease produced by this organism is clinically indistinguishable from classic cholera (Bhattacharya et al 1993) and the diagnosis in this study was made by culture and serotyping with 0 7 3 9 antiserum.…”
Section: Discussionmentioning
confidence: 91%